Electron microscopy: methods and pProtocols - Kuo, John (Methods in molecular biology, 2014)
Conventional Specimen Preparation Techniques For Transmission Electron Microscopy of Cultured Cells -- Microwave-assisted Processing and Embedding for Transmission Electron Microscopy -- Processing Plant Tissues for Ultrastructural Study -- Staining Sectioned Biological Specimens for Transmission Electron Microscopy: Conventional and En Bloc Stains -- Metal Shadowing for Electron Microscopy -- Freeze Fracture and Freeze Etching -- Conventional Specimen Preparation Techniques For Scanning Electron Microscopy of Biological Specimens -- High-pressure Freezing: Current State and Future Prospects -- Cryo-fixation by Self-pressurized Rapid Freezing -- Cryo-Electron Microscopy of Vitreous Sections -- Negative Staining and Cryo-negative Staining: Applications in Biology and Medicine -- Electron Microscopy of the Microtubule Cytoskeleton Assembly Vitro -- Cryosectioning Fixed and Cryoprotected Biological Material for Immmunocytochemistry -- Analysis of Specificity in Immunoelectron Microscopy -- Cryo-Electron Microscopy of Membrane Proteins -- Tracking DNA and RNA Sequences at High Resolution -- Visualization of DNA and Protein-DNA Complexes with Atomic Force Microscopy -- Biological Applications of Phase-Contrast Electron Microscopy -- Single Particle Cryo-Electron Microscopy And 3-D Reconstruction Of Viruses -- Electron Tomography for Organelles, Cells and Tissues -- Correlative Light and Electron Microscopy: from Live Cell Dynamic to 3D Ultrastructure -- Nanometer-resolution Fluorescence Electron Microscopy (Nano-EM) in Cultured Cells -- Correlative Fluorescence- and Electron Microscopy of Quantum Dot Labeled Proteins on Whole Cells in Liquid -- FIB-SEM Tomography in Biology -- Correlative Light and Electron Microscopy using Immunolabeled Sections -- Correlative 3D Imaging: CLSM and FIB-SEM Tomography Using High-Pressure Frozen, Freeze-Substitued Biological Samples -- Three-dimensional Imaging of Adherent Cells using FIB-SEM and STEM -- X-Ray Microanalysis in the Scanning Electron Microscope -- Application of SEM and EDX in Studying Biomineralization in Plant Tissues -- Freeze Stabilization and Cryopreparation Technique for Visualizing the Water Distribution in Woody Tissues by X-ray Imaging and Cryoscanning Electron Microscopy -- Biological Applications of Energy-Filtered TEM -- Secondary Ion Mass Spectrometry Imaging of Biological Cells and Tissues -- Elemental and Isotopic Imaging of Biological Samples using Nano SIMS -- 3D Chemical Mapping: Application of Scanning Transmission (soft) X-ray Microscopy (STXM) in Combination with Angle-Scan Tomography in Bio-, Geo- and Environmental Science.
Keywords: Elektronenmikroskopie